Analytical model for fiber-reinforced granular soils under high confining stresses - Shukla S.K.; Sivakugan N.; Singh A.K. (My University, 2025)
This technical note proposes a simple analytical model for predicting the shear strength behavior of fiber-reinforced granular soils under high confining stresses, where it can be assumed that pullout of fibers does not take place. The model presents an analytical expression derived from the force-equilibrium consideration incorporating several significant parameters describing the characteristics of the granular soil and the fibers, such as fiber content, aspect ratio, modulus of elasticity of fibers, specific gravity of fiber material, soil-fiber friction, initial orientation with respect to shear plane, normal confining stress, specific gravity of soil particles, angle of shearing resistance of soil, and void ratio of soil. The expression shows that inclusion of fibers in the granular soil induces cohesion, may be called apparent cohesion, as well as increase in normal stress on the shear failure plane, which are proportional to the fiber content and aspect ratio, implying that increase in shear strength is also proportional to the fiber content and aspect ratio. The results based on this model are discussed for some specific range of parameters in their practical ranges. It is observed that the increase in shear strength of the granular soil due to the presence of fibers is significantly contributed by the apparent cohesion, and the contribution to the shear strength from the increase in normal stress is limited. The model shows that the increase in shear strength follows the trends of variation as reported in some previous works. © 2010 ASCE.